Accessing information by voice - Tucker, Roger (Technical Centre for Agricultural and Rural Cooperation, 2007)
Getting up to date agricultural information to rural farmers has always been a challange, especially in areas with low literacy rates. A system to read out text, available via mobile phone, could help reach many more communities